Psychosocial determinants of attachment styles - Marchwicki, Piotr (Studia Psychologica: Theoria et praxis, 2004)
Attachment Styles and Sex, Parents' Education Level, and the Number of Siblings. Continuity of the Attachment Styles from Childhood to Adolescence: An Empirical Research. The present study investigates the links between attachment quality and sex and some variables of the family environment, such as father’s and mother's education level, the number of siblings, and the problem of the continuity of the attachment styles from childhood to adolescence. Measures of childhood attachment styles to both parents, adolescent attachment styles, along with a series of personal questions, were completed by a sample of 302 secondary school students (151 girls and 151 boys). When compared with the boys, the girls were less likely to adopt an avoidant attachment style to mother, while they were more likely to adopt secure and anxious/ambivalent adolescent attachment styles. Differences were also observed in the intensity of some attachment styles according to the father's (but not to the mother's) education level: the daugh rs of fathers with secondary education, in comparison with daughters of fathers with work and university education, tended to show a weeker intensity of both childhood and adolescent insecure attachment styles and a stronger intensity of the secure adolescent attachment style. Moreover, girls and boys with siblings were less likely to exhibit insecure (especially avoidant) childhood attachment styles to both parents than those who had no siblings. Both sexes seemed moderately likely to continue attachment models from childhood to adolescence.